Position of Coracoid Button Predicts Loss of Reduction in Acromioclavicular Joint Dislocation Patients Treated With the Suture-Button - Xian-Bin Yu; Tong Li; Wei Hu; Hua Chen; Yao-Sen Wu; Liao-Jun Sun (Journal of Investigative Surgery, 2021)
Background Loss of reduction is the most common complication after acromioclavicular (AC) joint dislocation treated with the suture-button. Some predictors of it are known, but finding new predictors is an ongoing process. In this study, we evaluate the importance of the position of the coracoid button. Materials and methods Between April 2010 and February 2017, 186 patients with AC joint dislocation were identified. All patients were managed with the same surgical technique and postoperative protocol. The position of the coracoid button was determined immediately after surgery by anterior–posterior views of the operated shoulder and was classified as medial (Group A, 42 cases), central (Group B, 85 cases) and lateral (Group C, 59 cases) positions. The main outcome measurement was loss of reduction. The main analysis was the association between the coracoid button position and loss of reduction. Results No significant difference was found in the baseline characteristics among 3 groups. During follow-up, there were 15 cases (35.7%) developing loss of reduction in Group A, 5 cases (5.9%) in Group B and 26 cases (44.1%) in Group C. The rate of loss of reduction in Groups A and C were higher than that in Group B (p < .05). Moreover, there was no significant difference in the rate of reduction loss between lateral and medial positions of the coracoid buttons (p > .05). Conclusion Our results indicated that both lateral and medial positions of the coracoid buttons could predict loss of reduction in AC joint dislocation patients treated with the suture-button.